Semi-rigid beam to column connection under static loading using abaqus - Norlina, Muhamad Nor (2014)
The connection of beam to column is very essential especially to transfer and distributes the load as well as contributing in the rigidity of the overall structures. A proper design of connection between members is very important for a steel structure to perform its best in sustaining load. As the performance of computers were increasing widely and the availability of computer software, the use of the finite element method (FEM) possible in the current research and design activity. The objectives of this study are to model and simulate a 3D beam to column connection under static loading; to understand the behavior of the connection from moment-rotation graph and obtained the displacement, stiffness and rotation from the graph as well as to determine the types of failure in the connection. This paper presents thesemi-rigid beam to column connections using fasteners by using the ABAQUS finite element software code; since Finite Element Analysis (FEA) offers the feasibility to simulate the actual behavior of the joints beam to column connection at low costs and short period of time compared with the experimental tests A specimen using top and seat angle (SRC-3A) over 6 specimens in previous experimental by Khaled and Suswanto in 2013 was simulated and tested using static loadmg and the results obtained after the numerical simulation were compared with the experimental data in order to validate the model. Based on the result analysis of moment-rotation, it can be concluded that the connection lies in semi-rigid even though the stiffness of the model in simulation is high compared to experimental which impact to the largest moment of capacity. Lastly, the modes of failure for specimen SRO-A have been determined which are due to buckling at column flange and plate exactly as in experimental.